The Argentine digital education curriculum: an analysis of the “critical” dimension of digital skills (Praxis Educativa, 2021)
In this article we analyze a corpus of documents belonging to the Digital Education curriculum launched in Argentina between years 2015 and 2019 as part of a broader reform, aimed at digital literacy and training in digital skills at school. The object of analysis of our study focuses in particular on the way in which the curricular texts conceptualize the critical dimension of digital skills. The methodology we have adopted articulates the content analysis approach with historical-anthropological educational ethnography, the latter being the theoretical-methodological framework that, in general, guides our study. As a theoretical framework, we recover the contributions made by the critical pedagogies on the competences curriculumand other developments developed by the field of educational technology and digital literacies. In the analysis, we stablish a dialogue between the curricular texts of the corpus and a series of broader technoeducational, pedagogical and cultural processes. Finally, we project an agenda of problems that is an alternative to the one dominant in the field of digital literacy.
Keywords: digital competences; curriculum; digital literacy; data literacy; digital education